Effects of Some Chelators and Surfactants on Hyperaccumulator Sedum alfredii Hance Remediating Contaminated Soil. Issue 8 (17th November 2019) - Dou, Xuekai; Dai, Huiping; Wei, Shuhe; Hu, Yahu; Skuza, Lidia
ABSTRACT: The effects of some chelators and surfactants on the hyperaccumulator Sedum alfredii Hance remediating co-contaminated soil contained 0.85 mgkg −1  Cd and 1.138 mg kg −1 PAHs (16 kinds of priority control polycyclic aromatic hydrocarbons by USEPA) were determined using soil pot culture experiment. Results showed that Cd capacity in shoot of S. alfredii was 16.88 µg pot −1 in treatment control 4 without additions. By contrast, Cd capacities in shoots were significantly increased by 37.6–270.9%, including CEDTA+SA, CEDTA+TW80, CSA+TW80+EDTA and CSA+TW80+CA as 216.6%, 42.4%, 84.0% and 65.4%, respectively. The degradation of PAHs in the rhizosphere of S. alfredii was significantly increased ( p < .05) by 24.1%, 27.9%, 20.6%, 30.5% and 24.9% for the treatment of CEDTA+SA, CEDTA+TW80, CCA+SA, CSA+TW80+EDTA and CSA+TW80+CA, respectively. Thus, the treatment of CEDTA+SA, CEDTA+TW80, CSA+TW80+EDTA and CSA+TW80+CA could significantly improve the accumulation of Cd in S. alfredii and also significantly increased PAH degradation in its rhizosphere, which was of great practical significance for phytoremediation of Cd-PAHs co-contaminated soil.